Distributed Data Integrity and Decentralized Storage Leveraging IPFS in Blockchain Systems - Ahmad Gunawan; Mungkap Mangapul Siahaan; Rendhika Adyatama; Toktar Kerimbekov; Kristina Vaher (Blockchain Frontier Technology, 2026)
In the digital era that increasingly relies on distributed systems, data integrity has become a major challenge for various technological platforms, ranging from cloud services to blockchain-based infrastructures. The dispersion of data across multiple nodes without centralized oversight increases the risk of manipulation, loss, and inconsistency. This study aims to evaluate the effectiveness of the InterPlanetary File System (IPFS) as a distributed data storage solution capable of maintaining data integrity in an automatic, efficient, and verifiable manner. The research method involves a literature review of 30 scientific references and a case study-based simulation conducted within a local network consisting of four active IPFS nodes. The tests include file uploads, verification of Content Identifiers (CID), simulation of node failures, and evaluation of system performance based on parameters such as security, efficiency, and scalability. The results indicate that IPFS successfully detects file changes through CID discrepancies, ensures continued data access despite node failures, and optimizes bandwidth usage via caching and replication mechanisms. In conclusion, IPFS offers a secure, scalable, and tamper-resistant approach to distributed data storage, making it highly relevant for modern digital systems requiring transparency, reliability, and strong data integrity guarantees.